Oral tribology of dairy protein-rich emulsions and emulsion-filled gels affected by colloidal processing and composition - Andrea Araiza-Calahorra; Alan R. Mackie; Anwesha Sarkar (Current Research in Food Science)
Designing nutritious food for the elderly population often requires significant quantities of leucine-rich whey proteins to combat malnutrition, yet high-protein formulations can cause mouth dryness and increased oral friction. This study investigated how various colloidal processing methods and compositions impact the in vitro oral tribological properties of protein-rich emulsions and emulsion-filled gels. Oil-in-water emulsions with oil fractions from 1 wt% to 20 wt% were prepared, alongside emulsion-filled gels containing whey protein isolate (WPI), hydrolysed whey protein (HWP), or a blend of both (10 wt% protein content). Two processing approaches were employed: creating emulsions with an initial 10 w% protein content (M1) and initially forming emulsions with 0.1 wt% protein content, then enriching to a final 10 wt% concentration (M2). The hypothesis was that formulations with HWP or method 2 (M2) would offer lubrication benefits by inducing droplet coalescence, aiding in the formation of a lubricating boundary tribofilm. Surprisingly, the tribological behavior of high-protein emulsions showed minimal dependence on oil droplet volume fraction. However, both HWP-based emulsions and those processed with M2 for WPI exhibited significant friction reduction, which may be attributed to the presence of coalesced oil droplets, supporting our hypothesis. Substituting 50 wt% of WPI with HWP in emulsion-filled gel boli resulted in very low friction coefficients in the boundary lubrication regime, suggesting oil droplet release from the gel matrix. These findings provide insights into designing high-protein foods with improved mouthfeel for the elderly population, necessitating further validation through sensory studies.